Photoprotective effect of botanicals and vitamins: A systematic review of clinical trials. (2nd November 2015) - Tuong, William; Kuo, Sandy; Sivamani, Raja K.
Abstract: Background : Overexposure to solar radiation is a major contributor to skin cancer development and premature skin aging. Botanical extracts and vitamins may represent novel photoprotective agents. Objective : We sought to systemically review clinical evidence for the use of botanically derived agents and vitamins as photoprotective agents. Methods : We systematically searched Embase and PubMed databases. Two independent reviewers reviewed abstracts for inclusion. Additional relevant studies were identified by a manual review of reference lists. Data from eligible studies were extracted independently and discrepancies were resolved by consensus. Results : A total of 51 studies met inclusion criteria. Limited available evidence indicates that several botanical agents and vitamins in topical or oral forms may have promising photoprotective effects. However, generalizability of results is limited by small sample sizes. Conclusion and relevance : Botanical extracts and vitamins may add to the armamentarium of sun-protective agents. Additional high-quality trials are needed to strengthen support for their use.